2019
DOI: 10.1111/pre.12373
|View full text |Cite
|
Sign up to set email alerts
|

New insights into the distribution of alien cyanobacterium Chrysosporum bergii (Nostocales, Cyanobacteria)

Abstract: SUMMARY Invasive and alien cyanobacteria are considered as a serious threat to aquatic ecosystems due to their ability to produce cyanotoxins and outcompeting native species. Among cyanobacteria, Nostocales is a group with strong competitive advantages including the production of resting cells, ability to fix nitrogen or high affinity to phosphorus. A species Chrysosporum bergii has broadened its original distribution from brackish and seawater habitats of Caspian and Aral Seas to northern regions of Europe. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Nutrient concentration and N:P ratio were not significant factors for C. bergii ( Table 1 ). Other studies indicated that C. bergii preferred low concentrations of inorganic phosphorus and the species was the most powerful competitor among Nostocales at moderate (19–20 °C) temperatures [ 24 , 44 ]. On the contrary, Savadova et al [ 29 ] revealed that the species has a preference for higher (26–30 °C) temperatures.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nutrient concentration and N:P ratio were not significant factors for C. bergii ( Table 1 ). Other studies indicated that C. bergii preferred low concentrations of inorganic phosphorus and the species was the most powerful competitor among Nostocales at moderate (19–20 °C) temperatures [ 24 , 44 ]. On the contrary, Savadova et al [ 29 ] revealed that the species has a preference for higher (26–30 °C) temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…According to Savadova et al [ 29 ], S. aphanizomenoides tolerated a wide range of temperatures (20–30 °C), and growth rate was one of the highest between tested native and alien cyanobacteria. These abilities probably predetermined increased proliferation and dominance of the species in temperate lakes [ 23 , 24 , 26 ]. The current experiment revealed that S. aphanizomenoides was a superior competitor over P. agardhii under elevated nutrient concentrations at 24 °C, but not in the case of A. gracile, which may suppress the establishment of alien cyanobacteria in temperate lakes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the genera belonging to the order Nostocales of cyanobacteria have the advantages of producing dormant cells and fixing nitrogen. Some members of this order are Cylindrospermopsis spp., Sphaerospermopsis spp., Cuspidothrix spp., and Chrysosporum spp., which have been reported to invade new habitats in various environments [ 2 , 6 , 7 , 8 ]. These invasive nostocalean cyanobacteria are filamentous organisms, which have some overlapping morphological characteristics with each other and with some non-invasive species.…”
Section: Introductionmentioning
confidence: 99%